Mean to Long-Term Clinical And Radiological Results Of Unlinked Total Elbow Arthroplasty - Hyytiäinen, Altti (My University, 2020)
Total elbow arthroplasty is mostly used for elbows mutilated by rheumatoid arthritis. Today there is two types of TEAs used: Semi-constrained, in which parts are mechanically linked, and unlinked, in which components are connected only by patients own tissue. These prostheses provide great results for improved elbow function and pain relief for patients with RA. In previous studies the complication rates for TEAs are much higher than in other common arthroplasties such as knee or hip. Most common complications for TEAs are loosening of components, periprosthetic fractures and instability. In our study we analyzed long-term clinical and radiological results of three different models of unlinked prosthesis. Total of 53 prostheses in 48 patients were included to our study. All patients had RA and were operated in two Finnish hospitals between 1997-2007. For the evaluation we used Mayo Elbow Performance Score (MEPS), range of motion (ROM) and radiographs taken before and after operations. Paired-Samples T-test was used to compare pre- and postoperative results and Kaplan-Meyer survival analysis was used to calculate survival times. In our study long- term MEPS scores and ROM were significantly higher postoperatively. Complications and revisions were much more common and survival time shorter than in other common arthroplasties. TEAs provide great long-term improvement for the patients’ quality of life. Yet the complication and revision rates are high and survival time relatively short and therefore development of new TEAs is needed.
Keywords: arthroplasty, elbow, rheumatoid arthritis, unlinked